Civic-militarized schools in Brazil: a state of knowledge in Brazil - Miranda, Edna Mara Corrêa (2023)
This article aims to present a state of knowledge about research carried out in Brazil on civic-military schools. It is an offshoot of a dissertation that investigated the curriculum of militarized schools in the Federal District defended in May 2021 in the Graduate Program in Education- Professional Modality (PPGE-MP) at the Faculty of Education of the University of Brasília-UnB.It was oriented around dissertations and theses of master's and doctorate located in the Thesis and Dissertations Databases of google academic sites, Scielo Network, Capes Database – Digital Library of Theses and Dissertations (BDTD) and an Institutional Repository. Fifteen papers were found, one thesis and fourteen dissertations. It was found that only the Midwest and Southeast regions have conducted research on the theme, showing that so far few researchers have been interested in the subject. The militarization of public schools proved to be an element of reflection of fields of knowledge that are beyond Education, such as Psychology, Social Sciences and Anthropology, however, it has not yet been verified in the inventoried researches the distinction between military and militarized institutions, a nerve point of policies and debates for the area.